Pengaruh Pemberian Fungi Mikoriza Pada Tanaman Kangkung (Ipomea Reptans Poir.) - Sitorus, Rumiris Fanessa; Anggraeni, Atika Puspita; Pulungan, M Farhan; Pulungan, Ahmad Shafwan S; Sarie, Marlinda Nilan (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
This research aims to determine the dose of mycorrhiza to increase the growth and production of water spinach plants (Ipomea reptans poir). The parameters observed were plant height and number of leaves. The research method used was RAL (Completely Randomized Design), by administering 5 treatments with doses (2.5 grams, 4 grams, 6 grams, 9 grams) and one control treatment. And each treatment with 3 repetitions. The plant height was 80 cm and the largest number of leaves was 36 in the P3 treatment (giving 6 grams of mycorrhiza). Giving a dose of mycorrhiza affects the growth of water spinach (Ipomea reptans poir).